2D TiS2 Layers: A Superior Nonlinear Optical Limiting Material. Issue 24 (4th October 2017) - Varma, Sreekanth J.; Kumar, Jitesh; Liu, Yang; Layne, Katherine; Wu, Jingjie; Liang, Chenglu; Nakanishi, Yusuke; Aliyan, Amir; Yang, Wei; Ajayan, Pulickel M.; Thomas, Jayan
Abstract: The advancement in high power lasers has urged the requisite of efficient optical limiting materials for both eye and sensor protection. The discovery of atomically thin 2D transition metal dichacogenides with distinctive properties has paved the way for a variety of applications including optical limiting. Until recently, the optical limiting effect exhibited by 2D materials is inferior to the benchmark materials fullerene (C60 ) and graphene. This article reports the optical limiting activity of the 2D transition metal dichalcogenide, titanium disulfide (TiS2 ) nanosheets, using optical and photoacoustic z‐scan techniques. The 77% nonlinear optical limiting exhibited by the TiS2 sheets with 73% linear‐transmittance is superior to that of any other existing 2D dichalcogenide sheets, graphene, and the benchmark optical limiting material, C60 . The enhanced nonlinear response is attributed to the concerted effect of 2‐photon and the induced excited state absorptions. By using photoacoustic z‐scan, a unique tool developed to determine the nonlinear optical limiting mechanism in materials, it is found that the optical limiting exhibited by TiS2 2D sheets and graphene are mainly due to nonlinear absorption rather than scattering effects. These results have opened the door for 2D‐dichalcogenide‐materials‐based highly efficient optical limiters, especially at low fluences. Abstract : 2D Dichalcogenide nanosheets are of great demand due to their incredible optical and electrical properties. 2D TiS2 nanosheets prepared by liquid‐phase exfoliation exhibit appreciable optical limiting properties and are found to be superior to the benchmark materials such as graphene and C60 . Nonlinear optical limiting is a concerted effect of 2‐photon absorption and induced excited‐state absorption.